A new approach to patient indexing. Issue 10 (October 1987) - Edwards, J C; Thompson, K; Jameson, D G
Abstract : A computer based rheumatology patient index is described. Patients are indexed according to essential clinical and laboratory data without reference to Procrustean diagnostic labels. The stored information can be searched for a wide range of practical and scientific purposes. The software was devised in the windows environment for the Apricot Xen for maximum speed and intelligibility.